Book Review: Milnes, Joan. (2003). Field Work Savvy: A Handbook for Students in Internship, Co-Operative Education, Service-Learning and other forms of Experiential Education. WA: Pleasant Word. - Gay Roland (Networks: An Online Journal for Teacher Research, 2003)
Field Work Savvy by Joan Milnes is a handbook for students preparing to participate in a field based learning experience. It is a user-friendly guide for high school and college level students. Ms. Milnes has researched the whys and hows of making a field experience successful for students and employers. This handbook provides the students' faculty coordinator with a comprehensive preparatory plan to ease the transition from the classroom to the world of work.